Progress in the understanding of C1q-like protein 4 (C1ql4) and its use in oncology - Qing, Zhang; Qing-Shan, Li; Wan-Yue, Han; Fan, Xu (Nepalese Journal of Cancer, 2022)
C1q and tumor necrosis factor (TNF)-related proteins (CTRPs) are a superfamily of proteins secreted in adipose tissues that are highly homologous to lipocalin. Previous studies have shown that this family has important biological functions in diseases such as metabolic disorders, cardiovascular diseases and inflammation in many types of tissues. C1q-like protein 4 (C1ql4) is one of the members of this family, which is mainly expressed in the testis and adipose tissue, and plays an important role in promoting angiogenesis, regulating lipid synthesis, inducting testosterone secretion, inhibiting ovarian granulosa cell apoptosis and myoblast fusion. This article reviews the current progress on molecular structure, tissue expression, and the main biological functions of C1ql4.